Recent advances in the development of CB1R selective probes - Amenta, Arianna; Caprioglio, Diego; Minassi, Alberto; Panza, Luigi; Passarella, Daniele; Fasano, Valerio; Imperio, Daniela (Frontiers in Natural Products, 2023)
Cannabinoid subtype 1 receptors (CB1Rs) are an important class of G protein-coupled receptors (GPCRs) belonging to the endocannabinoid system. CB1Rs play a crucial modulatory role in the functioning of other neurotransmitter systems and are involved in a wide range of physiological functions and dysfunctions; thus, they are considered one of the most important targets for drug development, as well as diagnostic purposes. Despite this, only a few molecules targeting this receptor are available on the pharmaceutical market, thus emphasizing the need to gain a deeper understanding of the complex activation pathways of CB1Rs and how they regulate diseases.As part of this review, we provide an overview of pharmacological and imaging tools useful for detecting CB1Rs. Herein, we summarize the derivations of cannabinoids and terpenoids with fluorescent compounds, radiotracers, or photochromic motifs. CB1Rs' molecular probes may be used in vitro and, in some cases, in vivo for investigating and exploring the roles of CB1Rs together with the starting point for the development of CB1R-targeted drugs.